Teaching Mathematically Promising Students: Insights from Classroom Practice - Lipovec, Alenka; Ferme, Jasmina (Selected Contemporary Research on Special Needs, Giftedness, and Talent in Slovenia, 2025)
This chapter explores how future primary school teachers engage with mathematically promising students. The study analysed 40 records from student teachers’ practical training, focusing on their experiences working with at least one mathematically promising pupil. The findings highlight key characteristics of mathematically promising students, including their proficiency in mathematical operations, ability to handle complex tasks, and intrinsic motivation. Future teachers employed a range of approaches, such as personalized teaching, supplementary activities, and problem-solving tasks. While many future teachers recognized the need for adaptive strategies, only half engaged students in problem-based or divergent thinking tasks. This limited use of advanced pedagogical methods indicates a need for further training to enhance instructional practices for mathematically promising students. These findings contribute to understanding the challenges and opportunities in educating mathematically gifted learners.